2008
DOI: 10.1021/cm071452e
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Films from Templated TiO2 and Structural Changes during their Thermal Treatment

Abstract: This work is focused on synthesis, characterization, and determination of main parameters of the multilayer P123 templated TiO 2 films. The mesoporous multilayer thin films consist of TiO 2 nanoparticles on the F-doped SnO 2 (FTO) conductive glass substrates. The films were grown by implementing the protocol of supramolecular templating with the amphiphilic triblock copolymer, Pluronic P123. The templated multilayer films were manufactured by repeated dip coating followed by the thermal treatment at 350 °C for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
76
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 27 publications
12
76
0
Order By: Relevance
“…However, the mesostructural shrinkage should be taken into account. Procházka et al [162] investigated the structural changes for the multilayered mesoporous TiO 2 films during thermal treatment. They found that the specific surface area and roughness factor of the calcined mesoporous TiO 2 films were not further increased after the deposition of more than 3-5 layers.…”
Section: Layer-by-layer Deposition Of Mesoporous Tio 2 Film Photoanodesmentioning
confidence: 99%
“…However, the mesostructural shrinkage should be taken into account. Procházka et al [162] investigated the structural changes for the multilayered mesoporous TiO 2 films during thermal treatment. They found that the specific surface area and roughness factor of the calcined mesoporous TiO 2 films were not further increased after the deposition of more than 3-5 layers.…”
Section: Layer-by-layer Deposition Of Mesoporous Tio 2 Film Photoanodesmentioning
confidence: 99%
“…[20,21] The use of clusters and nanoparticles as building blocks is an interesting strategy to fabricate organized mesoporous films containing crystalline species, [12] but it is very difficult to obtain multilayer films for further macroscale design. [22] As a special case, regularly arranged nanopillar films seem to be obtained by controlled thermal treatment (e.g., slow heating) for gradual crystallization of titania frameworks. [17,18] The nanopillar structures are interesting for managing porosity of anatase films (sufficient and relatively uniform mesospaces between the nanopillars).…”
Section: Introductionmentioning
confidence: 99%
“…17 Here, our films remain robust and crack free to thicknesses over 30 mm, in stark contrast to films fabricated directly using copolymer structure-directed sol-gel chemistries, where the single layer thickness is limited to less than one micrometre. 9,23 This entirely overcomes the issue of volume reduction, stress, and delamination in polymer directed, self-assembled films. In Fig.…”
Section: Solar Cell Performancementioning
confidence: 97%